Proposed classification scheme for the waste utilization value - Tio, Jacob Sy (1991)
Discriminant Analysis was used as a classificatory scheme for the (positive) waste utilization value of different wastes. A total of thirty (30) wastes was surveyed in Metro Manila. Sixteen (16) of these wastes were considered for study using the Discriminant Analysis module of the Statistical Package for Social Sciences (SPSS) program. Eight (8) variables or factors were identified and measured for each of the waste: Availability, Separation, Handling, Product, Demand, Cost, Technology and Profit. Stepwise discriminant analysis resulted in the rejection of two (2) variables: Availability and Product factors. Three (3) variables: Separation, Handling and Demand factors have significant contribution in the classification of WUV. The overall classification rate is 93.75%.